MOBILE PHONES OF HEALTH CARE PROFESSIONALS: A POTENTIAL THREAT TO INFECTION CONTROL IN A TERTIARY CARE HOSPITAL - Manikandan, Karthik; M, Jeya; S, Sasikala (International Journal of Clinical and Biomedical Research, 2017)
Background: Nosocomial infections are a major problem in both developed and developing countries. Among various reasons for the increase in the rate of nosocomial infections, the role of mobile phones used by Health Care Professionals (HCPs), is analyzed in this study. Aims and Objectives: To screen the surfaces of mobile phones of HCPs for pathogenic and nonpathogenic bacteria and to compare it with the control group. To study the significance of mobile phones of HCPs acting as vehicles for transmitting nosocomial infections. Materials and Methods: 200 HCPs (Doctors, nurses, medical students, and technicians) 50 other than HCPs mobile phone surfaces are swabbed with sterile swabs soaked in sterile saline and inoculated onto Blood agar and Mac Conkey agar and incubated for 48 hours. The organisms are identified by the colony morphology and characteristic biochemical reactions. Control group (50) comprised of general public and arts and science students. A questionnaire related to their habit of using the cell phones was also filled up by both the test group and the control group. Results: The pathogenic bacteria isolated from study group are Staphylococcus aureus, which is predominant, followed by E. coli, Klebsiella, Pseudomonas aeruginosa andProteus mirabilis. The non- pathogenic bacteria isolated are Micrococci, Coagulase Negative Staphylococci, Diphtheroids, Neisseria catarrahlis, Aerobic spore bearers, and Candida albicans. The prevalence of Pathogenic bacteria and Non Pathogenic bacteria are higher in HCPs samples when compared with the control group. KEY WORDS: Nosocomial infections; Mobile phones; Health care professionals.